2017
DOI: 10.1111/nyas.13442
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical signals protect stem cell lineage selection, preserving the bone and muscle phenotypes in obesity

Abstract: The incidence of obesity is rapidly rising, increasing morbidity and mortality rates worldwide. Associated comorbidities include type 2 diabetes, heart disease, fatty liver disease, and cancer. The impact of excess fat on musculoskeletal health is still unclear, although it is associated with increased fracture risk and a decline in muscular function. The complexity of obesity makes understanding the etiology of bone and muscle abnormalities difficult. Exercise is an effective and commonly prescribed non-pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 201 publications
(257 reference statements)
0
8
0
Order By: Relevance
“…148 ) and nuclear factor erythroid 2-related factor 2 (NRF2) 147 , a critical transcriptional regulator of antioxidant protein expression, which protects against oxidative damage. These low-intensity signals also served to protect the actual number of satellite cells (precursors to differentiated skeletal muscle cells) available within the muscle when challenged with endocrinopathy 149 or obesity 150 .…”
Section: Ageing Exercise and Muscle Phenotypementioning
confidence: 99%
“…148 ) and nuclear factor erythroid 2-related factor 2 (NRF2) 147 , a critical transcriptional regulator of antioxidant protein expression, which protects against oxidative damage. These low-intensity signals also served to protect the actual number of satellite cells (precursors to differentiated skeletal muscle cells) available within the muscle when challenged with endocrinopathy 149 or obesity 150 .…”
Section: Ageing Exercise and Muscle Phenotypementioning
confidence: 99%
“…However, recent research has shown that mild hyperthermia actually supports the differentiation of satellite cells and stem cells, a crucial step in the late proliferation and early remodeling phases of healing [42,43]. Although the optimal Hong Z et al 12 9 Llion et al 38 6 Barakat AS et al 15 5 Ellefsen et al 53 7 Aydogdu et al 31 6 Gilsanz et al 56 5 Anandkumare et al 32 9 Lohman et al 58 6 Mutlu et al 34 9 Simão et al 59 7 D'Souza et al 36 6 Wang et al 60 9 procedure (i.e., time, duration, temperature, and intervals) for controlled hyperthermia has not been confirmed, research by Guo et al demonstrated pilot results in which the observed moderate hyperthermia at the late inflammatory phase upregulated the production of myofibril proteins through the late stages of myogenesis. Additionally, the results showed an induced differentiation of myotubes over 72 hours compared to cells that were not exposed to mild hyperthermia [44].…”
Section: Moderate Hyperthermia Inductionmentioning
confidence: 99%
“…Low-intensity vibration (LIV) has been shown to promote stem cell differentiation toward osteoblastogenesis and away from adipogenesis, giving it the potential to be used as an alternative for exercise until a patient can tolerate load-bearing capacity [58]. Additionally, vibration therapy has been demonstrated to be beneficial for treating sarcopenia [56].…”
Section: Vibration Therapymentioning
confidence: 99%
“…Frechette et al. () report that low‐intensity vibration biases stem cell differentiation toward osteoblastogenesis and away from adipogenesis, making this intervention a non‐invasive means of building bone and muscle and preventing the formation of fat. One of the earliest reports of MV influence on obesity in a high‐fat diet‐induced obesity model (C57BL/6 mice) demonstrated that 12 weeks of treatment was able to reduce subcutaneous and visceral fat in the obese animals concurrent with increased bone marrow MSCs with decreased adipogenic differentiation capability (Luu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite general agreement that mechanical signals play a central role in fat distribution, the ideal characteristics of an effective loading regimen or the molecular cues that control the adaptive responses are still poorly understood (Engler et al 2006;Sen et al 2011). Frechette et al (2017) report that low-intensity vibration biases stem cell differentiation toward osteoblastogenesis and away from adipogenesis, making this intervention a non-invasive means of building bone and muscle and preventing the formation of fat. One of the earliest reports of MV influence on obesity in a high-fat diet-induced obesity model (C57BL/6 mice) demonstrated that 12 weeks of treatment was able to reduce subcutaneous and visceral fat in the obese animals concurrent with increased bone marrow MSCs with decreased adipogenic differentiation capability (Luu et al 2009).…”
Section: Discussionmentioning
confidence: 99%